Oxidized phospholipid and transcriptomic signatures of THC-related vaping associated lung injury - Tomeka L. Suber; Mohammadreza Tabary; William Bain; Tolani Olonisakin; Karina Lockwood; Zeyu Xiong; Yingze Zhang; Naina Kohli; Lauren Furguiele; Hernán Peñaloza; Bryan J. McVerry; Jason J. Rose; et al. (Scientific Reports)
Abstract E-cigarette/vaping-associated lung injury (EVALI) is strongly associated with vitamin E acetate and often occurs with concomitant tetrahydrocannabinol (THC) use. To uncover pathways associated with EVALI, we examined cytokines, transcriptomic signatures, and lipidomic profiles in bronchoalveolar lavage fluid (BALF) from THC-EVALI patients. At a single center, we prospectively enrolled mechanically ventilated patients with EVALI from THC-containing products (N = 4) and patients with non-vaping acute lung injury and airway controls (N = 5). BALF samples were analyzed by Luminex multiplex assay, RNA sequencing, and mass spectrometry. After treating BEAS-2B lung epithelial cells with vaping and non-vaping BALF, LDH release was quantified. THC-EVALI BALF had significant increases in IFNγ, CCL2, CXCL5, and MMP2 relative to non-vaping patients. RNA sequencing showed enrichment for biological oxidation, glucuronidation, and fatty acid metabolism pathways. Oleic acid and arachidonic acid metabolites were increased in THC-EVALI, as were oxidized phosphatidylethanolamines (PE) such as PE(38:4). THC-EVALI BALF induced more LDH release compared to BALF from non-vaping patients. Thus, THC-EVALI is characterized by altered phospholipid composition, accumulation of lipid oxidation products, and increased pro-inflammatory mediators that may contribute to epithelial cell death. These findings serve as a framework to study novel oxidized phospholipids implicated in the pathogenesis of EVALI.